Novel variants in EDNRB gene in Waardenburg syndrome type II and SOX10 gene in PCWH syndrome. (January 2021) - Varga, Lukas; Danis, Daniel; Drsata, Jakub; Masindova, Ivica; Skopkova, Martina; Slobodova, Zuzana; Chrobok, Viktor; Profant, Milan; Gasperikova, Daniela
Abstract: Waardenburg syndrome (WS) is a clinically and genetically heterogeneous group of inherited disorders manifesting with sensorineural hearing loss and pigmentary anomalies. Here we present two Caucasian families with novel variants in EDNRB and SOX10 representing both sides of phenotype spectrum in WS. The c.521G>A variant in EDNRB identified in Family 1 leads to disruption of the cysteine disulfide bridge between extracellular segments of endothelin receptor type B and causes relatively mild phenotype of WS type II with low penetrance. The novel nonsense variant c.900C>A in SOX10 detected in Family 2 leads to PCWH syndrome and was found to be lethal. Highlights: Mutations in EDNRB are rarely associated with Waardenburg syndrome type 2 with low penetrance. Novel variant (c.900C > A) in SOX10 gene was found to be lethal in early childhood. Whole exome sequencing is a useful tool for detection of novel variants in complex syndromes.